(untitled) (International Educators Conference, 2025)
This article explores the importance of the portrait method in artistic psychologism and its various forms of expression. It analyzes the static and dynamic types of the portrait method, as well as the roles of dynamic, typological, and analytical methods in portraying characters’ inner worlds and psychological states. By providing examples from world and Uzbek prose, it shows how the portrait method effectively reflects characters’ external appearances and internal changes. In conclusion, the portrait method is an important tool for vividly and fully expressing characters in literary works, significantly enhancing readers’ interest in the text.